Correlation between hs-CRP-triglyceride glucose index and NAFLD and liver fibrosis - Yuhui Zhou; Hao Lin; Xiaochun Weng; Huifang Dai; Jing Xu (BMC Gastroenterology)
Abstract Background The novel serum high-sensitivity C-reactive protein-triglyceride glucose index (CTI) has been recognized as an optimal parameter encompassing both insulin resistance (IR) and inflammation, which are potential mechanisms contributing to non-alcoholic fatty liver disease (NAFLD). This study aims to examine the correlation between CTI and NAFLD/liver fibrosis in American adults. Methods This is a cross-sectional study utilizing data from NHANES during the period from 2017 to 2020. The composite CTI was calculated through the formula: 0.412×Ln [(high-sensitivity C-reactive protein(hs-CRP)] + Ln(triglycerides × fasting plasma glucose/2). To explore the correlation between CTI and NAFLD/liver fibrosis, multivariate logistic regression analyses, subgroup analyses, restricted cubic spline (RCS) regression, and receiver operating characteristic (ROC) analysis were employed. Results Among 3,488 participants, 42.7% (n = 1,488) were diagnosed as NAFLD, while 9.4% (n = 329) exhibited liver fibrosis. Logistic regression and RCS regression analyses demonstrated a significant positive linear correlation between CTI and the prevalence of NAFLD (OR = 1.94, 95% CI: 1.70, 2.22) as well as liver fibrosis (OR = 1.38, 95% CI: 1.14, 1.67), even after being adjusted for potential confounding variables. Furthermore, a significant correlation between CTI and the prevalence of NAFLD/liver fibrosis was observed across various subgroups. ROC analysis revealed that CTI can serve as a more robust identify for the prevalence of NAFLD (AUC = 0.756) and liver fibrosis (AUC = 0.702) compared to triglyceride glucose index (TyG) and hs-CRP alone. Conclusion Elevated levels of CTI are directly associated with significant liver fibrosis and the presence of NAFLD, indicating its potential utility as a biomarker for liver fibrosis and NAFLD.